Pengaruh Lifestyle Dan Brand Trust Tehadap Kepuasan Konsumen Serta Dampaknya pada Loyalitas Pelanggan Scraf Produk Buttonscraves di Kabupaten Kuningan - Irnawati Irnawati (Journal on Education, 2023)
The purpose of this study is to analyze the influence of lifestyle on customer loyalty, analyze the influence of brand trust on customer loyalty, analyze the effect of satisfaction on loyalty, analyze the influence of lifestyle on customer satisfaction, analyze the influence of customer brand trust on customer satisfaction, analyze the effect of customer satisfaction in mediating the influence of lifestyle on loyalty, overcome customer satisfaction in mediating the influence of brand trust against customer loyalty. The population in the study was members of Bs Lady who represented Buttonscraves consumers living around Kuningan Regency as many as 130 members of Bs Lady. The sampling technique uses a non-propobality sampling technique with a type of purposive sampling. Purposive sampling is a sampling pattern according to criteria considerations. The calculation of the number of samples using the slovin formula with an error rate or percentage of inaccuracy that can still be tolerated by 5% obtained a sample of 130 members of Bs Lady. The results of the study are Lifestyle has a positive and insignificant effect on customer loyalty, Brand trust has a positive and significant effect on customer loyalty, Customer satisfaction has a positive and significant effect on customer loyalty, lifestyle has a positive and significant effect on customer satisfaction, Brand trust has a significant positive effect on customer satisfaction, customer satisfaction is able to mediate lifestyle on customer loyalty, customer satisfaction able to mediate brand trust and customer loyalty